2012
DOI: 10.1007/s12026-012-8272-z
|View full text |Cite
|
Sign up to set email alerts
|

The rhapsody of NLRPs: master players of inflammation … and a lot more

Abstract: The Nucleotide-binding oligomerization domain, Leucine-rich Repeat and Pyrin domain containing (NLRP) family and corresponding inflammasomes are important intracellular sensors of microbial pathogens and stress signals that promote caspase-1-mediated release of IL-1β and IL-18. Studies using targeted disruption of NLRP1 and NLRP3 have revealed key roles for these inflammasomes in innate immunity and inflammation, as well as in autoimmune diseases, metabolic disorders, and cancers. The newly identified family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 105 publications
0
53
0
1
Order By: Relevance
“…Several NLRs, including NLRP6, NLRC4 and NLRP3, associate with the ASC inflammasome to trigger caspase-1 activation and IL-1b secretion following stimulation with different pathogens (55). We observed that NLRC4 and NLRP6 were dispensable for the caspase-1 activation after T. cruzi infection, whereas in the absence of NLRP3, the IL-1b production and caspase-1 activation were significantly reduced.…”
Section: Discussionmentioning
confidence: 77%
“…Several NLRs, including NLRP6, NLRC4 and NLRP3, associate with the ASC inflammasome to trigger caspase-1 activation and IL-1b secretion following stimulation with different pathogens (55). We observed that NLRC4 and NLRP6 were dispensable for the caspase-1 activation after T. cruzi infection, whereas in the absence of NLRP3, the IL-1b production and caspase-1 activation were significantly reduced.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, we detected a significant amount of IL-1b in Nlrp3 2/2 BMMs compared with uninfected BMMs, which suggests that additional receptors are involved in P. brasiliensis-mediated caspase-1 activation. Because Asc interacts with several NLRs, including Nlrp6 (36), Nlrp10 (37), and the intracellular AIM2 receptor (38-41), we speculated that these receptors may interact with Asc and cooperate with Nlrp3 in stimulating an efficient innate immune response against P. brasiliensis. Notably, our study using an experimental model of P. brasiliensis infection showed a significant abnormal phenotype in the inflammasome-deficient mice, providing in vivo support to our in vitro findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IL-1b production occurs in two steps: pro-IL-1b synthesis is triggered by pattern recognition receptor ligation, leading to NF-kB activation, before being cleaved by inflammasome-activated caspase-1 to produce the active cytokine (7). The NLRP3 inflammasome is activated by diverse stimuli, including microbial molecules, host-derived molecules associated with stress or danger, and crystalline or particulate substances (8,9); many of these are also able to induce complement activation.…”
mentioning
confidence: 99%